Nutritional Status Among Hospitalized Chronic Kidney Disease Patients in Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Despite being underdiagnosed, malnutrition is a Chronic Kidney Disease (CKD) consequence that has been shown to impact prognosis and quality of life. It is linked to mortality and a quick development to End-Stage Renal Disease (ESRD). Death and the rate of ESRD progression will be slowed down by early detection and therapy.  Data regarding the dietary health of patients with Chronic Kidney Disease (CKD) are scarce in Bangladesh. This study sought to ascertain the frequency and pattern of malnutrition among CKD patients receiving hospital care.Materials and methods: It was a hospital-based cross sectional observational study, conducted at the Department of  Nephrology and Medicine of Chittagong Medical College Hospital for a six-month period from April 2017 to September 2017. Ninety-seven hospitalized CKD patients were selected purposively as per set inclusion and exclusion criteria. Nutritional status was assessed by Body Mass Index (BMI) Mid-Upper Arm Circumference (MUAC) Triceps Skinfold Thickness (TSF) Arm Muscle Circumference (AMC) and serum albumin.  Results: The mean age of the population was 49.15 years (SD ± 14.16) with male and female ratio being 1.85:1. More than 90% were in stage 5 of CKD. Based on the diagnostic criteria applied, the patients' frequency of malnutrition varied greatly, ranging from 15.5% to 97.9% of the population. It was highest by the AMC criteria in 97.9% of the patients, followed by 92.8% by TSF, 80.4% by MUAC, 56.7% by serum albumin and 15.5% by BMI.  Conclusion: Undernutrition is really common among chronic kidney disease patients in Bangladesh.JCMCTA 2024 ; 35 (1) : 100-106